Case Report: Penile Strangulation Secondary to Hair Tourniquet - Rawls, William F.; White, Jeffrey T.; Mohamed, Ahmad; Peppas, Dennis; Rosenberg, Eran (Frontiers in Pediatrics, 2020)
Penile strangulation is a rare condition in children caused by circumferential constriction of the coronal sulcus by constricting material, commonly thin maternal hair. Vague presenting symptoms often makes diagnosis difficult, but delay in diagnosis can lead to a variety of severe complications including urethral injury and penile necrosis. Providers must have a high index of suspicion and carry out a careful examination to identify maternal hair strands that may bury deep within penile edema. We describe two cases of penile strangulation secondary to maternal hair strands that were successfully treated with thorough examination and ligation of the constricting hair in the emergency department. In both cases, presentation involved penile swelling and erythema which was noticed by caregivers. Once the diagnosis has been made, urgent treatment using depilatory cream or mechanical removal must occur, with urgent referral to specialists if unable to remove to constricting material. Caregivers must also be counseled on appropriate steps to prevent penile hair tourniquet syndrome. Devastating complications can be avoided by early recognition and proper management of the syndrome, but providers must have knowledge of the condition and a high index of suspicion.